New trends in concrete-polymer composite materials and systems - Czarnecki, Lech (2009)
Appropriate combination of polymers and classical construction materials provides opportunities for innovative applications and systems, for improved performance and for increased durability. Particularly in restoration and retrofitting, polymer based materials highly contribute to sustainable construction activity. This paper highlights the innovations, new approaches and durability assessments, presented at the International Symposium on Polymers in Concrete in Guimarães, Portugal, 2006. Emphasis is put on microstructure formation, modification by means of hardener free epoxy resin by polymers in solution or by recycled particles, bond assessment and improvement, durability of bond under moisture and temperature effects, concrete protection by means of coatings.